ANALISIS PERBEDAAN DIVIDEN PADA PERUSAHAAN KELUARGA DAN NON KELUARGA BERDASARKAN KEPEMILIKAN ULTIMAT - Cahyani, Krisnati Adi; Sanjaya, I Putu Sugiartha (Modus Journals, 2014)
This study aims to to analyze whether there is a diference of the dividend shared on family company and non family based on the ultimate ownerships. Sampling method that used in this research was 400 manufacturing companies which are listed at Indonesia Stock Exchange (IDX), with research periods 2009-2012. The sample collected by purposive sampling method. Secondary data obtained from a IDX database and the ownership structure obtained through Sanjaya’s (2010) previous research. The result of data analysis shows there are signifcant and diferences of the dividend shared between family company and non family. Family company pay dividends lower than non family company.Keywords : Dividend, Agency Teory, Family Ownership, IDX